Aromatic amine N-oxide organometallic compounds: searching for prospective agents against infectious diseases1. Issue 32 (28th August 2015) - Rodríguez Arce, Esteban; Mosquillo, M. Florencia; Pérez-Díaz, Leticia; Echeverría, Gustavo A.; Piro, Oscar E.; Merlino, Alicia; Coitiño, E. Laura; Maríngolo Ribeiro, Camila; Leite, Clarice Q. F.; Pavan, Fernando R.; Otero, Lucía; Gambino, Dinorah
<x xml:space="preserve">Abstract</x> 1, 1′-Bis(diphenylphosphino)ferrocene pyridine-2-thiolato-1-oxide Pd(ii) and Pt(ii) hexafluorophosphate compounds showed cytotoxicity on T. cruzi and M. tuberculosis.